How and When Do Leaders Influence Employees’ Well-Being? Moderated Mediation Models for Job Demands and Resources - Berger, Rita; Czakert, Jan Philipp; Leuteritz, Jan-Paul; Leiva, David (Frontiers in Psychology, 2019)
Following the call of recent reviews on leadership and well-being, the purpose of this study is to examine how and when two contrasting leadership styles, transformational (TFL) and passive-avoidant leadership (PAL), are related to employees’ anxiety and thereby either promote or inhibit employees’ well-being. Using the prominent Job Demands-Resources model (JD-R model) as a theoretical framework, we propose that the relationship between leadership behavior and anxiety is mediated by organizational job demands, namely role ambiguity, and job resources, namely team climate for learning (TCL), as well as moderated by autonomy as important job characteristic. A sample of 501 knowledge workers, working in teams in a German research and development (R&D) organization, answered an online survey. We tested moderated multiple mediation models using structural equation modeling. Results demonstrated that the relationships between TFL as well as PAL on the one hand and anxiety on the other hand were fully mediated by role ambiguity and TCL. Job autonomy moderated the quality of the leadership – job demand relationship for TFL, and PAL. This paper contributes to understanding the complex relationship between leadership and followers’ well-being taking into account a combination of mediating and moderating job demands and resources. This is the first study that examines the effects of TFL and PAL on well-being taking into account the job demand role ambiguity and team processes and autonomy as resources.